A physiological study on a commercial reef fish to quantify the relationship between exploitation and climate change resilience - Duncan, Murray Ian (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2019)
The persistence of harvested fish populations in the Anthropocene will be determined, above all, by how they respond to the interacting effects of climate change and fisheries exploitation. Predicting how populations will respond to both these threats is essential for any adaptive and sustainable management strategy. The response of fish populations to climate change is underpinned by physiological rates and tolerances, and emerging evidence suggests there may be physiological-based selection in capture fisheries. By quantifying important physiological rates of a model species, the endemic seabream, Chrysoblephus laticeps, across ecologically relevant thermal gradients and from populations subjected to varying intensities of commercial exploitation, this thesis aimed to 1) provide the first physiologically grounded climate resilience assessment for a South African linefish species, and 2) elucidate whether exploitation can drive populations to less physiologically resilient states in response to climate change. To identify physiologically limiting sea temperatures and to determine if exploitation alters physiological trait distributions, an intermittent flow respirometry experiment was used to test the metabolic response of spatially protected and exploited populations of C. laticeps to acute thermal variability. Exploited populations showed reduced metabolic phenotype diversity, fewer high-performance aerobic scope phenotypes, and a significantly lower aerobic scope curve across all test temperatures. Although both populations maintained a relatively high aerobic scope across a wide thermal range, their metabolic rates were compromised when extreme cold events were simulated (8 Â°C), suggesting that predicted future increases in upwelling frequency and intensity may be the primary limiting factor in a more thermally variable future ocean. The increment widths of annuli in the otoliths of C. laticeps from contemporary and historic collections were measured, as a proxy for the annual growth rate of exploited and protected populations. Hierarchical mixed models were used to partition growth variation within and among individuals and ascribe growth to intrinsic and extrinsic effects. The best model for the protected population indicated that the growth response of C. laticeps was poorer during years characterised by a high cumulative upwelling intensity, and better during years characterised by higher mean autumn sea surface temperatures. The exploited population growth chronology was too short to identify an extrinsic growth driver. The growth results again highlight the role of thermal variability in modulating the response of C. laticeps to its ambient environment and indicate that the predicted increases in upwelling frequency and intensity may constrain future growth rates of this species. A metabolic index (Ï•), representing the ratio of O2 supply to demand at various temperatures and oxygen concentrations, was estimated for exploited and protected populations of C. laticeps and used to predict future distribution responses. There was no difference in the laboratory calibrations of Ï• between populations, and all data was subsequently combined into a single piecewise (12 Â°C) calibrated Ï• model. To predict the distribution of C. laticeps, Ï• was projected across a high-resolution ocean model of the South African coastal zone, and a species distribution model implemented using the random forest algorithm and C. laticeps occurrence points. The future distribution of C. laticeps was estimated by predicting trained models across ocean model projections up to 2100. The best predictor of C. laticeps' current distribution was minimum monthly Ï• and future predictions indicated only a slight range contraction on either edge of C. laticeps' distribution by 2100. In order to provide policy makers, currently developing climate change management frameworks for South Africa's ocean, with a usable output, the results of all research chapters were combined into a marine spatial model. The spatial model identified areas where C. laticeps is predicted to be resilient to climate change in terms of physiology, growth and distribution responses, which can then be prioritised for adaptation measures, such as spatial protection from exploitation. While these results are specific to C. laticeps, the methodology developed to identify areas of climate resilience has broad applications across taxa. From a global perspective, perhaps the most salient points to consider from this case study are the evidence of selective exploitation on physiological traits and the importance of environmental variability, rather than long-term mean climate changes, in affecting organism performance. These ideas are congruent with the current paradigm shift in how we think of the ocean, selective fisheries, and how they relate to organism climate resilience.
Keywords: Chrysoblephus laticeps -- Climatic factors; Chrysoblephus laticeps -- Physiology; Sparidae -- South Africa -- Climatic factors; Reef fishes -- South Africa -- Climatic factors; Fish populations -- South Africa -- Climatic factors; Fish populations -- Measurement; Fish populations -- Monitoring; Fisheries -- South Africa -- Environmental aspects; Ocean temperature -- Physiological effect -- South Africa